Further Defining the 2012 Multi-Society Task Force Guidelines for Surveillance of High-risk Adenomas: Is a 3-Year Interval Needed for All Patients?. Issue 9 (October 2019) - Grunwald, Douglas; Landau, Alex; Jiang, Zhenghui G.; Liu, Joy J.; Najarian, Robert; Sheth, Sunil G.
Abstract : Goals: We set out to determine whether variation from this 3-year follow-up interval was associated with the finding of subsequent high-risk adenoma (HRA). Background: HRAs include the following: (1) an adenoma measuring ≥10 mm, (2) ≥3 adenomas found during a single procedure, and (3) an adenoma with high-grade dysplasia or villous architecture. The current Multi-Society Task Force guideline for timing of surveillance colonoscopy after removal of a HRA is 3 years. Study: In 2016, we analyzed 495 patients who had a HRA removed during a 2008 colonoscopy. We compared the frequency of finding another HRA at follow-up intervals. We used the current guidelines as our referent group and performed logistical regression to identify whether any patient characteristics, procedural factors, or type of HRA predicted the development of HRAs on follow-up colonoscopy. Results: Individuals who followed-up at a median of 4.5 years did not have more HRA on follow-up compared with those who followed-up at 3 years (25.2% vs. 21.0%, P =0.062). These groups had similar baseline characteristics. Older individuals, male gender, having a history of polyps, and piecemeal resection of an HRA predicted future HRAs. The removal of ≥3 adenomas in 2008 as well as a combination of multiple, large, and advanced polyps showed a higher risk of future HRAs. Conclusions: The 2012 Multi-Society Task Force recommendation of 3-year follow-up after removal of HRAs may not apply to all patients. We showed that a combination of patient demographics, procedural factors, and pathology best determines the surveillance colonoscopy interval. Abstract : Supplemental Digital Content is available in the text.